Undocumented workers' transitions : legal status, migration, and work in Europe - McKay, Sonia; Markova, Eugenia; Paraskevopoulou, Anna. (New York : Routledge, 2011)
"This book explores how immigration laws, while aimed at discouraging undocumented migration, actually sustain it. It documents the circumstances that have caused previously documented migrants to become undocumented and explores the impact of their changing status on their families and on their own employment opportunities. The authors argue that undocumented migrants are forced into the most precarious types of work, and changes in the way that employment is organised, with a shift into temporary, agency and sub-contracted work, makes undocumented migrants particularly attractive in some employment markets. This groundbreaking volume draws substantially on data collected from a two-year research study in seven European countries that was focused on understanding the impact of migration flows on EU labour markets"--
Includes bibliographical references (p. [169]-180) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Foreign workers -- Europe -- Case studies; Illegal aliens -- Europe -- Case studies; Electronic books